1979
DOI: 10.1159/000128092
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Microsphere Method for Determination of Cardiac Output and Flow Distribution in the Rat

Abstract: The radioactive microsphere technique was applied to determine simultaneous cardiac output and flow distribution in the rat. Left ventricular injections of large numbers of microspheres were given, without significant adverse effects, allowing determination of flow to organs and tissues with low perfusion rates. In order to determine coronary blood flow it was necessary to excise the inner lining of the left ventricle, thus eliminating activity from deposits of microspheres. Cardiac output determination showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 13 publications
(31 reference statements)
1
19
0
Order By: Relevance
“…The ECG was monitored during injection of microsphere boluses to exclude untoward effects, and HR was noted every 5 min during infusions. CO and selected organ and tissue flows were determined using standard methods and a reference organ withdrawal rate of 0.62 ml X min-1 -for details see Idvall et al [14], Carbonized microspheres labelled with 85Sr and Mice were given as injected boluses and isotope activ ity measured with a double-channel gamma well scin tillation counter (Selectronic, model 54-22). The whole or part of the following organs were examined: stomach, duodenum, small intestine, cecum, colon, pancreas, spleen, liver, testes, anterior abdominal wall skin and skeletal muscle (from the uncatheterized thigh region).…”
Section: Determinations and Presentation O F Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ECG was monitored during injection of microsphere boluses to exclude untoward effects, and HR was noted every 5 min during infusions. CO and selected organ and tissue flows were determined using standard methods and a reference organ withdrawal rate of 0.62 ml X min-1 -for details see Idvall et al [14], Carbonized microspheres labelled with 85Sr and Mice were given as injected boluses and isotope activ ity measured with a double-channel gamma well scin tillation counter (Selectronic, model 54-22). The whole or part of the following organs were examined: stomach, duodenum, small intestine, cecum, colon, pancreas, spleen, liver, testes, anterior abdominal wall skin and skeletal muscle (from the uncatheterized thigh region).…”
Section: Determinations and Presentation O F Resultsmentioning
confidence: 99%
“…CVPs were also registered simultaneously using this catheter. A PE 50 catheter was established in the right superficial femoral artery and used to record BP (groups A and B) and connected to a constant withdrawal pump (Sage 351) as the reference organ in group C. In this latter group, the right carotid artery was catheterized, PE 50, and used to inject microsphere boluses -for details see Id vail et al [14] -as well as to record BP. A soft silicon catheter (OD 0.63 mm) was used to cannulate both the left main thoracic lymph duct in group A -for details see Saldeen and Linder [25], and the portal vein via its gastroduodenal branch in group B.…”
Section: Experimental Preparationmentioning
confidence: 99%
“…In the first series, we demonstrated that there was no significant difference in sphere densities between the right and the left hind limb, indicating adequate blood mixing. In a recent study, 450,00015-~m microspheres were injected in 291 g rats corresponding to 1,546 spheres/g rat [6].…”
Section: Discussionmentioning
confidence: 99%
“…In this investigation we have studied collateral capacity after occlusion of one main lower limb artery. To quantitate maximum vascular conductance, microsphere distribution in the lower limb muscles after microsphere injections into the aortic root was determined in the hyperemic phase after 5 min of ischemia [4,6,7]. Ischemia was produced by inflating a cuff around the rat pelvis for 5 min.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that in small animals such injection results in good mixing of the microspheres in the arterial blood allowing determination of regional blood fl ow [40] . Although the catheter through which the microspheres were injected necessitated ligation of the right common carotid artery, we found no difference in blood fl ow between the right and left cerebral hemispheres either during normoxia or during hypoxia.…”
Section: Methodologiesmentioning
confidence: 99%